Synthesis of multicomponent carbides by the vacuum-free electric-arc method; Nanobiotechnology Reports; Vol. 18, iss. 1 - Gumovskaya A. A. Arina Andreevna; Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna; Pak A. Ya. Aleksandr Yakovlevich; Mamontov G. Ya. Gennady Yakovlevich (2023, 2023)
Title screen